Pratique et enseignement de l’audiovisuel en géographie - Marie Chenet; Luisa Simoes; Quentin Laurent (EchoGéo)
Since the beginning of the 20th Century, the geographers use audiovisual methods, through frame analysis or film direction as part of their researches. Therefore, they had to train in audiovisual tools and methods. The paper presents first a short history of geographers who directed films. Then the contribution of audiovisual in geographical researches is treated. Lastly, the formation in video offered to the geography student in the University Paris 1 is presented.